2020
DOI: 10.1007/s00296-020-04549-w
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of cervical spine involvement in rheumatoid arthritis patients in the era of biologics: a real-life, cross-sectional MRI study

Abstract: Cervical spine involvement may lead to severe complications in rheumatoid arthritis (RA). In the era of modern therapies, atlantoaxial subluxation (AAS) may be rare; however, it may still be detected in asymptomatic patients. The onset of myelopathy can occur at any time. Altogether 49 female RA patients were included. Among them, 15 were methotrexate treated, biologic free, while 34 patients received biologics. The patients had no cervical pain or any neurological symptoms. We assessed the first (C1) and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…The most serious complication of cervical spine arthritis is subluxations. Recent studies showed that anterior AAS was present in 18–32% of patients [ 8 , 12 , 13 ], whereas in our study, it was diagnosed in 58% of patients by radiographs, most likely because the study was conducted in a reference center for rheumatic diseases. Usually, AADI (anterior atlanto-dental interval) higher than 6 mm is considered for surgery [ 14 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The most serious complication of cervical spine arthritis is subluxations. Recent studies showed that anterior AAS was present in 18–32% of patients [ 8 , 12 , 13 ], whereas in our study, it was diagnosed in 58% of patients by radiographs, most likely because the study was conducted in a reference center for rheumatic diseases. Usually, AADI (anterior atlanto-dental interval) higher than 6 mm is considered for surgery [ 14 ].…”
Section: Discussioncontrasting
confidence: 69%
“…In the current study, at the C1/C2 level, pannus was seen in 21% of patients, showing postcontrast enhancement in 5% of the patients, periodontal effusion in 11%, and BME in 5%. Another study showed similar results; the prevalence of pannus formation was almost 25% [ 13 ]. Carotti at al.…”
Section: Discussionmentioning
confidence: 56%
“…In approximately 20-70% of patients, C-spine lesions develop 10-11 years after disease onset, but in some individuals they may occur early and lead to instability. This condition, if untreated, may cause myelopathy with neurological deficits [ 2 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Atlanto-axial subluxations, especially of the anterior type, are the most frequently encountered anomalies with an incidence varying between 18% and 32% of cases (Baek et al, 2021;Oláh et al, 2020;Yurube et al, 2012).…”
mentioning
confidence: 99%